Knowledge management and decision making - Kaklauskas, Artūras; Zavadskas, Edmundas Kazimieras; Šaparauskas, Jonas (Technological and Economic Development of Economy, 2004)
Knowledge management definitions are presented in the paper. The types of capital acknowledged by modern economics theory and their relationship to knowledge management are investigated. It is emphasized that recently organizations pay more attention to personnel, their knowledge management, but not to technologies, i.e. organizations realize that effective knowledge management is vital to effective existence of a company. Direct relation of knowledge management to decision making is analyzed.Article in Lithuanian.Žinių valdymas ir sprendimų priėmimasFirst Published Online: 21 Oct 2010